Exploring Perceptions of University Students Pertaining to Grades over Knowledge and Skills (Journal of Education and Educational Development, 2020)
The aim of the research was to study the phenomenon surrounding the perspective of university students preferring grades to knowledge and skills. Three currently enrolled participants were selectedfrom different private universities of Karachi. Participants’ interviews were examined through thematic analysis. The findings suggested that students give preference to grades and knowledge, more job oriented focusof the study and made recommendations for institutions and academicians for further probing of the issue in hand.